High‐Performance Photodetectors Based on Organometal Halide Perovskite Nanonets. (6th February 2017) - Wang, Wenhui; Ma, Yurong; Qi, Limin
Abstract : The booming development of organometal halide perovskites has prompted the exploration of morphology‐engineering strategies to improve their performance in optoelectronic applications. However, the preparation of optoelectronic devices of perovskites with complex architectures and desirable properties is still highly challenging. Herein, novel CH3 NH3 PbI3 nanonets and nanobowl arrays are fabricated facilely by using monolayer colloidal crystal (MCC) templates on different substrates. Specifically, highly ordered CH3 NH3 PbI3 nanonets with high crystallinity are fabricated on a variety of flat substrates, whereas regular CH3 NH3 PbI3 nanobowl arrays are produced on a coarse substrate. The photodetection performance of the CH3 NH3 PbI3 nanonet‐based photodetectors is significantly enhanced compared to the photodetectors based on conventional CH3 NH3 PbI3 compact films. Particularly, the nanonet photodetectors exhibit a high responsivity (10.33 A W −1 under 700 nm monochromatic light), which is six times higher than that for the compact CH3 NH3 PbI3 film devices, fast response speed, and good stability. Owing to the two‐dimensional arrayed structure, the CH3 NH3 PbI3 nanonets exhibit an enhanced light harvesting ability and offer direct carrier transport pathways. Meanwhile, the MCC template brings about larger grain sizes with enhanced crystallinity. Furthermore, the perovskite nanonets can be formed on a flexible polyethylene terephthalate substrate for the fabrication of promising flexible nanonet photodetectors. Abstract : Highly ordered CH3 NH3 PbI3 nanonets with high crystallinity are fabricated on a variety of flat substrates through a facile nanosphere lithography approach. When used as a photodetector, the perovskite nanonet exhibits significantly enhanced photoresponsive performance owing to the unique net‐like architecture that is beneficial to light harvesting and charge collection.